Fisher folk organisations in the Caribbean : briefing note on networking for success - McConney, Patrick (CRFM Secretariat Belize CityBZ, 2007)
Provides the background and rationale for these organizations at the local, national and regional levels to facilitate their participation in the fisheries governance process. Notes the benefits to the fishermen and others in having such organisations, as well as the issues affecting their formation and development. Outlines the draft guidelines and strategy for the conducting of the national consultations for the launch of National Fisher Folk Organisations in Group Two countries and the establishment of the National Fisher Folk Organisation Network.